2016
DOI: 10.1126/science.aah5557
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of rubidium cations into perovskite solar cells improves photovoltaic performance

Abstract: All of the cations currently used in perovskite solar cells abide by the tolerance factor for incorporation into the lattice. We show that the small and oxidation-stable rubidium cation (Rb) can be embedded into a "cation cascade" to create perovskite materials with excellent material properties. We achieved stabilized efficiencies of up to 21.6% (average value, 20.2%) on small areas (and a stabilized 19.0% on a cell 0.5 square centimeters in area) as well as an electroluminescence of 3.8%. The open-circuit vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

75
3,145
3
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 3,365 publications
(3,239 citation statements)
references
References 39 publications
75
3,145
3
16
Order By: Relevance
“…In all kinds of dopants, the alkali metal cations (Na + , K + ) have been chosen to be the positive additive owing to their stability or resistance against oxidation and reduction 46. Herein, we found that alkali‐metal‐cation additives effectively improved the perovskite film with fewer GBs and traps states, enhanced the built‐in potential, attributing to higher power conversion efficiency (PCE) via assembling device.…”
Section: Introductionmentioning
confidence: 99%
“…In all kinds of dopants, the alkali metal cations (Na + , K + ) have been chosen to be the positive additive owing to their stability or resistance against oxidation and reduction 46. Herein, we found that alkali‐metal‐cation additives effectively improved the perovskite film with fewer GBs and traps states, enhanced the built‐in potential, attributing to higher power conversion efficiency (PCE) via assembling device.…”
Section: Introductionmentioning
confidence: 99%
“…Considering this effect, a variety of approaches have been explored to protect against moisture and hydrolysis from the preparation process of perovskite devices. Substantial effort has been made to improve the stability of perovskites by adapting the recipe of the precursor and designing protective capping layers on top of the perovskite film 19, 20, 21, 22, 23. To achieve this aim, previous work has traditionally been performed under dry fabrication conditions to protect the perovskite precursor and to prevent moisture from contacting films during various stages of processing—typically by processing in glove boxes with parts per million levels of H 2 O 1, 24.…”
mentioning
confidence: 99%
“…To achieve this aim, previous work has traditionally been performed under dry fabrication conditions to protect the perovskite precursor and to prevent moisture from contacting films during various stages of processing—typically by processing in glove boxes with parts per million levels of H 2 O 1, 24. In addition, compatible anhydrous solvents have to be chosen to obtain highly efficient and reproducible perovskite photovoltaics 19, 22, 25. Thus, developing fabrication procedures and perovskite precursors with low moisture sensitivity is not only crucial for achieving high‐efficiency perovskite devices, but is also important for facilitating the commercialization of perovskite photovoltaic devices and enabling greater tolerance for fabrication in air.…”
mentioning
confidence: 99%
“…Long term stability is the most important issue that impedes the perovskite based solar cells from rapid commercialization. The environmental and thermal stability of these materials can be improved by several methods like using modified perovskite structures which replaces the organic cation with cesium and rubidium 77, 78, 79. These modifications can not only improve the overall stability of the solar cell but also enhance the efficiency to a great extent.…”
Section: Fiber‐shaped Energy Harvesting Devicesmentioning
confidence: 99%